Selection of the Shortest Path of Gamalama Eruption Evacuation Using the Astar Method - Muhammad, Fitri; Kapita, Syarifuddin N; Mubarak, Abdul (Jurnal Improsci, 2024)
Natural disasters have no time limit and can happen anywhere at any moment. They put human life at risk and can result in both property loss and casualties. Like those at Gamalama volcano, volcanic eruption disasters are constant and incur enormous losses. There are numerous evacuation sites for self-rescue against volcanic eruptions, and knowing the distance to the evacuation sites is necessary to expedite the self-rescue process to reduce the number of victims. Naturally, the areas surrounding the disaster center must be kept clear. To solve this issue, a mechanism for choosing the shortest path via the astar method must be implemented. As part of the astar method, the shortest path is chosen by first figuring out the starting and destination locations, initializing intersections by turning each intersection into a node, adding the node to the open list, calculating it with weights, adding it to the closed list, figuring out potential nodes that lead to the destination, and saving the results. As a consequence of the master method's application, the shortest route—a distance of 3,560 meters—connects the starting point (the Tubo village head office) with the gathering point (the Salerno field). Bypassing every pre-planned path, which is as follows: No. 1 (Jl. Ake Tubo, Tubo) - Node 2 (Ake et al.) - Node 7 (Jl. Batu Angus No.1, Dufa Dufa) - Node 8 (North Sangaji) - Node 9 (Toboleu, Kec. Kota Ternate Utara) - Assembly Point (Salero Field). Keywords: Astar, Volcanic Disaster, and Geographic Information System.